Comparative analysis of vaginal natural orifice transluminal endoscopic surgery versus transumbilical laparoendoscopic single‐site surgery in ovarian cystectomy. Issue 2 (16th December 2020) - Huang, Lu; Lin, Yong‐Hong; Yang, Yue; Gong, Zhao‐Lin; He, Li
Abstract: Aim: To objectively assess the safety, feasibility, advantages and disadvantages and health economics benefits of vaginal natural orifice transluminal endoscopic surgery (vNOTES) versus transumbilical laparoendoscopic single‐site surgery (TU‐LESS) in ovarian cystectomy. Methods: We retrospectively analyzed the data of all patients in our hospital who had undergone vNOTES and TU‐LESS ovarian cystectomy due to 'unilateral ovarian cyst' from March 2019 to May 2020. Patients were classified into vNOTES group (86) and TU‐LESS group (210) based on surgical paths. The patients' general characteristics and perioperative outcomes were compared. Results: All 296 patients completed surgery with no need to switch to conventional laparoscopy or laparotomy procedures. There were no complications of Grade III, IV, V in Clavien‐Dindo classification. There were two patients in the vNOTES group and four patients in the TU‐LESS group with complications of Grade I, all of whom were treated with antipyretic drugs for postoperative fever. One patient in the TU‐LESS group presented the complication of Grade II and was treated with blood transfusion due to postoperative anemia. The two groups had similar general characteristics. Perioperative outcomes: The visual analogue scale (VAS) scores 24 h postoperation were significantly lower in the vNOTES group than in the TU‐LESS group. The cosmetic scores were significantly higher in the vNOTES group than in the TU‐LESS group. Postoperative stay and time of flatus after surgery were significantly shorter in the vNOTES group than in the TU‐LESS group. There was not significant statistical differences between the two groups in operation time, estimated blood loss, Hb decrease at 48 h postoperation, maximum body temperature in 48 h after surgery and hospital costs. Conclusion: It was proved to be safe and feasible in ovarian cystectomy by vNOTES. It worked better than TU‐LESS in relieving postoperative pain, shortening postoperative stay and improving cosmetic effects and so on. As an emerging surgical path, large sample multicenter randomized controlled trials are required to further verify its safety and advantages.